Insertional footprint of achilles tendon on calcaneal tuberosity in South Indian population: A cadaveric study - Vetrivel Chezian Sengodan; Mugundhan Moongilpatti Sengodan; Anjana Muralidharan Sushama (National Journal of Clinical Anatomy, 2023)
Background: Pathologies related to the Achilles tendon (AT) and its insertion are a very prevalent problem. A thorough understanding of its anatomy would assist us to develop and fine-tune treatment options for the same. Hence, a study was done to identify the anatomical footprint of the insertion of AT on the calcaneal tuberosity (CT). Methodology: A cadaveric study was conducted, in which 27 human lower limbs (18 cadavers) were dissected to determine the insertion site of all three fascicles of the AT on the CT. The width of the insertion and thickness of the AT 1 cm proximal to the insertion were also calculated. Results: Rotation of AT, presence of three individual fascicles for each muscle belly, and insertion of these fascicles were consistent throughout the 27 lower extremities dissected. The average width of its insertion is 26.62 mm, with a standard deviation (SD) of 1.98 mm. The average thickness of the AT 1 cm proximal to the insertion was found to be 8.06 mm with a SD of 2.18 mm. Conclusion: These findings are of worth to the ankle and foot surgeons for a better understanding of the insertional tendinopathies and partial thickness tears of AT to design better surgical options for its repair and modulate the conservative management in terms of physiotherapy to the South Indian population.